PERAN PROFITABILITAS SEBAGAI VARIABEL PEMODERASI PENGARUH KEBIJAKAN DIVIDEN DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN - Khoirunnisa Cahya Firdarini; Zulkifli; Achmad Tjahjono (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2023)
This study aims to examine the role of profitability as a moderating variable of dividend policy and debt policy on company value in Basic Industrial and Chemical sector companies listed on the Indonesia Stock Exchange during the period 2016 to 2020. The research method used in this study is a quantitative method based on financial statement data of companies that are the study population. The total sample in this study was 100 firm years. The sampling method using purposive sampling techniques and presenting the hypothesis used in this study is multiple linear regression analysis. The hypothesis proposed in this study is the effect of dividend policy on company value, the effect of debt policy on company value and the effect of profitability as a moderating variable for the effect of dividend policy and debt policy on company value. Dividend policy and debt policy are proven to affect company value; profitability is also proven to be able to moderate dividend policy to company value but not proven to moderate debt policy to company value.